Enabling Authentic Assessment: The Essential Role of Information Literacy. Issue 4 (8th November 2017) - Gunasekara, Chrys; Gerts, Carole
Abstract: We report on a study of an authentic assessment task in an Australian business school, where the 2015 ACRL framework for information literacy was applied to support the development of critical thought. Contextualised in an ongoing, meaningful partnership between a liaison librarian and an academic, the study involved pre- and post-engagement evaluation of learners' decision-making about information sources that would best support a business presentation to a senior executive team. The pre- and post-evaluations were mediated by engagement with learners on the constructed and contextual nature of authority, which involved a detailed set of guidelines and online discussion facilitated by an information services librarian and the academic convening the subject. We found that students are already sensitive to a constructivist paradigm in selecting information sources. However, the depth of critical enquiry in evaluating 'authority' was uneven. Notwithstanding the robustness of the guidelines that we developed to support the evaluation of information sources, we found that it is important to provide further support to learners in working through the application of a constructivist frame.